Football (Soccer) in Africa Origins, Contributions, and Contradictions - Ayuk, Augustine E. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This volume provides an analysis of the history, origins, and development of football in Africa. It brings together an edited assemblage of essays that describe and analyse football in nine African countries, including Cameroon, DRC, Egypt, Ghana, Kenya, Nigeria, Senegal, South Africa, and Uganda, from a social science perspective. The selection of these countries highlights the three major foreign languages and powers that have governed the continent; The English, the French, and Arabic, and provides a prism through which to analyze and compare how football developed in the various countries throughout Africa. This comparative methodology allow readers to identify similarities and differences in the progression of the game on the continent, and by focusing on football, an important relic of European colonialism in Africa, underscores the continued dependence on, and domination of Europeans on the Africans. In situating the genesis of the game, contributors examine and analyze the history, development, management, and mismanagement by bureaucrats at the political level as well as at various football federations throughout the continent.
1. Introduction, Ayuk E. Augustine -- 2. FIFA and Football Development in Africa , Wycliffe W.S. Njororai -- 3. The Confederation of African Football (CAF): Managing One of Africa's Most Vital Intergovernmental Organizations -- 4. Football in Cameroon, Best of Times, Worst of Times: Exploring the Paradox of Africa's Venerable Football Nation -- 5. Vicious Cycle: Cameroon(ization) and/or Foreign(ization) of the Indomitable Lions' s Coach -- 6. Football in the DR Congo: A Critical Account of "Congolese Football -- 7. The Egyptian Football and Politics -- 8. The History and Development of Football in Ghana -- 9. The Politics of Soccer Management in Kenya: The Rise and Decline of a Popular Sport -- 10. Soccer and Laamb (Senegalese Wrestling): Competing Sports, National Pride, Spectatorship, and Wealth in Senegal -- 11. Contradictions Within the South African Football Association and the Premier Soccer League -- The Origins, Status, Contributions, and Contradictions of Association Football in Uganda. .
Keywords: Sports-Sociological aspects; Ethnology-Africa.; Culture; Africa-History.; Imperialism; Sport Sociology; African Culture; African History; Imperialism and Colonialism